Development of a microfluidic paper based with portable system for glucose concentration colorimetric analysis - Ridho Irwansyah; Muhammad Bintang Herdian; Yudan Whulanza (BKS-TM Indonesia, 2025)
Diabetes mellitus is a major health problem in Indonesia, with a prevalence of up to 20.4 million people in 2024 according to the International Diabetes Federation (IDF). Early detection of blood sugar is hampered by expensive and difficult-to-access diagnostic tools. Microfluidic paper-based analytical devices (μPADs) are a potential solution because they are inexpensive, portable, and environmentally friendly, in accordance with WHO ASSURED standards. This study aims to develop a μPAD integrated with a portable detection system for colorimetric quantification of glucose concentration using Glucose Oxidase–Peroxidase Aminoantipyrine (GOD-PAP) reagent, which produces a color change proportional to glucose concentration. Initial testing was conducted on phosphate-buffered saline (PBS) and D-glucose solutions as test materials in glucose concentration research. The test materials will be validated using spectrophotometry. Next, the test materials will be applied to μPAD for colorimetric observation using an RGB sensor on a portable device. The quantification results show that the red ratio at 10 minutes of the colorimetric method has excellent linearity (R² = 0.96). Precision validation of the colorimetric method produced an RSD value of less than 5%. The paired t-test produced a p-value of 0.42 with a 95% confidence level, indicating that there was no significant difference between the glucose concentration quantification results obtained using the colorimetric method and the spectrophotometric method.